1993
DOI: 10.1164/ajrccm/147.4.793
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Pulmonary Function in Farmer's Lung: A Five-year Follow-up Study

Abstract: The recovery of pulmonary function in farmer's lung (FL) was studied during a 5-yr follow-up in 101 patients (20 men and 81 women, mean age 47 yr). At the initial evaluation all patients had the first diagnosed attack of FL. Spirometry, measurement of pulmonary diffusing capacity, and arterial blood gas analysis were done at the time of the diagnosis and 1, 3, 6, 12, and 24 months thereafter. The last follow-up measurements were made 4 to 6 yr after the initial evaluation. Mean FVC improved significantly for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
3
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 13 publications
5
35
3
2
Order By: Relevance
“…In our study the prevalence of asthma was low before the onset of farmer's lung and there was an increased incidence of asthma during the first years after an episode of farmer's lung. This finding confirms previous findings with smaller groups of patients (3)(4)(5).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study the prevalence of asthma was low before the onset of farmer's lung and there was an increased incidence of asthma during the first years after an episode of farmer's lung. This finding confirms previous findings with smaller groups of patients (3)(4)(5).…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of smokers among farmer's lung patients is low (3,7,12). The mean age and gender distribution of farmer's lung patients in this study were close to those of 2 other Finnish follow-up studies (3,7).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nonspecific bronchial hyperresponsiveness [226,227] and wheezing may also be prevalent in subjects with recent hypersensitivity pneumonitis, especially in dairy farmers [228,229].…”
Section: Environmental or Occupational Exposurementioning
confidence: 99%
“…Diffusing capacity of the lung for carbon dioxide is usually the slowest parameter to improve; defects in diffusing capacity of the lung for carbon dioxide may persist depending on stage of disease at diagnosis. 40,41 Smoking may also negatively influence outcome. 42 Vourlekis et al 33 also demonstrated that older age, smoking, and fibrosis all contribute to increased mortality compared with patients with nonhypersensitivity pneumonia.…”
Section: Commentmentioning
confidence: 99%